Sustained Muscle Deoxygenation vs. Sustained High VO(2) During High-Intensity Interval Training in Sprint Canoe-Kayak - Paquette, Myriam (Front Sports Act Living, 2019)
Recent data suggests that peripheral adaptations, i.e., the muscle ability to extract and use oxygen, may be a stronger predictor of canoe-kayak sprint performance compared to VO(2)max or central adaptations. If maximizing the time near VO(2)max during high-intensity interval training (HIIT) sessions is believed to optimize central adaptations, maximizing the time near maximal levels of muscle desaturation could represent a critical stimulus to optimize peripheral adaptations. Purpose: Therefore, the purpose of this study was to assess the VO(2), muscle oxygenation and cardiac output responses to various HIIT sessions, and to determine which type of HIIT elicits the lowest muscle oxygenation and the longest cumulated time at low muscle O(2) saturation. Methods: Thirteen well-trained canoe-kayak athletes performed an incremental test to determine VO(2)max and peak power output (PPO), and 4 HIIT sessions (HIIT-15: 40x[15 s at 115%PPO, 15 s at 30%PPO]; HIIT-30: 20x[30 s at 115%PPO, 30 s at 30%PPO]; HIIT-60: 6x[1 min at 130%PPO, 3 min rest]; sprint interval training (SIT): 6x[30 s all-out, 3 min 30 rest]) on a canoe or kayak ergometer. Portable near-infrared spectroscopy monitors were placed on the Latissimus dorsi (LD), Biceps brachii (BB), and Vastus lateralis (VL) during every session to assess changes in muscle O(2) saturation (SmO(2), % of physiological range). Results: HIIT-15 and HIIT-30 elicited a longer time >90%VO(2)max (HIIT-15: 8.1 ± 6.2 min, HIIT-30: 6.8 ± 4.6 min), compared to SIT (1.7 ± 1.3 min, p = 0.006 and p = 0.035) but not HIIT-60 (4.1 ± 1.7 min). SIT and HIIT-60 elicited the lowest SmO(2) in the VL (SIT: 0 ± 1%, HIIT-60: 8 ± 9%) compared to HIIT-15 (26 ± 12%, p < 0.001 and p = 0.007) and HIIT-30 (25 ± 12%, p < 0.001 and p = 0.030). SIT produced the longest time at >90% of maximal deoxygenation in all 3 muscles, with effect sizes ranging from small to very large. Conclusions: Short HIIT performed on a canoe/kayak ergometer elicits the longest time near VO(2)max, potentially conducive to VO(2)max improvements, but SIT is needed in order to maximize muscle deoxygenation during training, which would potentially conduct to greater peripheral adaptations.